Rare bird documentation form for Northern Goshawk at Seven Bridges County Park in 1981 - Moore, Francis L.et al (1981)
Rare bird documentation form for a Northern Goshawk at Seven Bridges County Park in Bremer County, IA on November 21, 1981. Epson - sheet feed